Dynamics of Social Conflict in Inter-Ethnic Marriage: A Case Study Of The Marriage Of The Indigenous Peoples Of Java And Lampung In Sungkai Barat North Lampung - Indrawan, Ghosel; Mukhlisin, Ahmad; Arsyad, Mufid (STAINI Press, 2026)
This study examines the social conflict dynamics in interethnic marriages between Javanese and Lampung communities, the factors triggering conflicts, and the adaptation and resolution strategies employed by couples. The research aims to understand how differences in culture, customs, and daily habits affect couples’ relationships and extended families, as well as how conflicts are managed. The study employs a qualitative approach with a case study design, collecting data through in-depth interviews, participatory observation, and documentation of the respective ethnic customs. The findings indicate that conflicts arise from differences in gender roles, family hierarchy, expressions of respect, and traditional ceremony practices, exacerbated by limited social tolerance and subjective judgments from the surrounding community. Adaptation strategies include open discussions, mutual understanding of each other’s culture, seeking guidance from family members, and adjusting habits to achieve harmony. Properly managed conflicts strengthen the relationship, enhance mutual understanding, and increase couples’ commitment.